Efforts to Enhance Student Activeness through the Reward and Punishment Model in the Third Grade of Elementary Schools - Qona'ah, Annisya'; Rondli, Wawan Shokib; Kironoratri, Lintang (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Student discipline in the learning process is one of the factors that can change student learning outcomes, and so does student activeness. The background of this research was the low activeness of students in the learning process in class. This study aimed to determine student activeness through the reward and punishment model. The method used in this research was classroom action research (CAR) conducted at the State Elementary School 2 Getas Pejaten, Jati Sub-district, Kudus Regency, by taking third-grade students as subjects. A total of 19 students, consisting of 12 male and 7 female students, were involved in these two cycles of classroom action research. Data collection techniques were carried out through interviews and observation with eleven indicators of activeness. The study results proved that the application of the reward and punishment model could increase the activeness of third-grade students at the State Elementary School 2 Getas Pejaten from the Pre-Cycle with a percentage of 60.78%, which increased in Cycle I with a presentation of 68.42% to Cycle II with a presentation of 83.73%. The effectiveness of this learning model can be used as a recommendation for class teachers. Hence, it can be concluded that the reward and punishment model can attract students' attention in the learning process.